Dynamics of Power and Cooperation in Rural Development: The Case of Chianina Beef Production in Italy - Kanemasu , Yoko; Sonnino, Roberta (The International Journal of Sociology of Agriculture and Food, 2009)
This article contributes to the theorization of the much-debated ‘paradigm shift’ from conventional agri-industrialism towards sustainable rural development through the adoption of an actor-oriented approach that focuses on the practices, initiatives and experiences of rural actors themselves. Building on existing conceptualizations of rural actors as active agents, we analyse cooperative relations amongst quality meat producers in central Italy to shed light onto the dynamics of their collective interventions. Our case study demonstrates that seemingly ‘alternative’ rural development processes do not necessarily represent a smooth transition towards a new paradigm. Whilst producers have the capacity to collectively negotiate the pressures of the conventional agri-food system, their agency encompasses also conscious attempts to manoeuvre a highly ambiguous relationship with conventional markets to their advantage. Such ‘empowerment’ is also far from unproblematic. Collective actions provide producers with a degree of power, which, however, is subject to an asymmetrical distribution that seems to parallel that of agri-industrialism. In other words, producers’ collective action against the dominant forces of agro-industrial globalization is a contested process of allocation of power over productive relations and the market. Our analysis hence problematises the notion of ‘paradigm shift’ and calls for further research that critically examines the power differentials that reside in different dimensions of rural development practices.